Balneotherapy Research in France - Roques, Christian François (Anales de Hidrología Médica, 2012)
In France, several public and/or private scientific investigation bodies are involved in balneotherapy scientific investigation (academic or university-linked institutes in Paris, Nancy, Bordeaux, Grenoble, Clermont-Ferrand, Toulouse; private bodiess in Paris, Aix les Bains, Saujon). However, these last years, the important development in medical balneotherapy investigation could be related to the AFRETH creation. The main data obtained these last years are presented in this paper: main results of the clinical trials and methodological comments.
Keywords: Balneotherapy Research; Crenotherapy Research; Clinical Trials; France